Fiber Cell-Specific Expression of the VP16-Fused Ethylene Response Factor 41 Protein Increases Biomass Yield and Alters Lignin Composition - Nakata, Miyuki T.; Sakamoto, Shingo; Nuoendagula,; Kajita, Shinya; Mitsuda, Nobutaka (Frontiers in Plant Science, 2021)
Arabidopsis thaliana transcription factors belonging to the ERFIIId and ERFIIIe subclade (ERFIIId/e) of the APETALA 2/ethylene response factor (AP2/ERF) family enhance primary cell wall (PCW) formation. These transcription factors activate expression of genes encoding PCW-type cellulose synthase subunits (CESA) and other genes for PCW biosynthesis. In this study, we show that fiber-specific expression of ERF035-VP16 and ERF041-VP16, which are VP16-fused proteins of ERFIIId/e members, promote cell wall thickening in a wild-type background with a concomitant increase of alcohol insoluble residues (cell wall content) per fresh weight and monosaccharides related to the PCW without affecting plant growth. Furthermore, in the ERF041-VP16 lines, the total amount of lignin and the syringyl (S)/guaiacyl (G) ratio decreased, and the enzymatic saccharification yield of glucose from cellulose per fresh weight improved. In these lines, PCW-type CESA genes were upregulated and ferulate 5-hydropxylase1 (F5H1), which is necessary for production of the S unit lignin, was downregulated. In addition, various changes in the expression levels of transcription factors regulating secondary cell wall formation were observed. In conclusion, fiber cell-specific ERF041-VP16 improves biomass yield, increases PCW components and alters lignin composition and deposition and may be suitable for use in future molecular breeding programs of biomass crops.